Aplikasi Pemberian Minuman Sereh Madu (Serdu) sebagai Pengembangan Fitofarmaka dalam Mengatasi Hipertensi pada Wanita - Rahayu, Trio Gustin; Khotimah, Husnul (Faletehan Health Journal, 2024)
Herbal therapy of boiled lemongrass and honey water is one alternative treatment in lowering blood pressure. This study aimed to determine the effectiveness of lemongrass honey (Ina. serdu) herbal therapy on hypertension in women. The research design used a pre-experiment one group pre-test post-test. The study was conducted in Serang City, Banten Province, namely at the Singandaru Health Center working area with a sample of 25 respondents. The sampling technique was quota sampling. Data analysis used the Wilcoxon signed rank test with a significance level of 95% (α 0.05). The results showed that on the 7th day of giving lemongrass honey (serdu) herbal drinks there was a decrease in systolic blood pressure (p value <0.001) and diastolic blood pressure (p value <0.001). An alternative choice for the treatment of women's hypertension is lemongrass honey drinks. However, further research was needed to ensure the effectiveness and safety of lemongrass honey drink in long term, especially for mothers who suffer from certain medical conditions.